The Influence of Miners' Knowledge and Behavior on Environmental Management at PT. Daka Group - Taupan , Muh.; Abbas , Bakhtiar; Supriaddin , Nofal (PT. Riset Press International, 2024)
Human activities based on economic benefits and environmental conservation have an important role in sustainable development. Improving the quality of human life through income from mining activities has both positive and negative impacts on the environment. PT Daka Group as a mining company faces environmental problems due to its activities. To overcome this negative impact, knowledge and environmentally friendly behavior of miners are needed. This study aims to analyze the influence of miners' knowledge and behavior on environmental management at PT Daka Group, filling the knowledge gap regarding the relationship. The methodology used is the census method with a population of 60 miners at PT Daka Group, with data collection through questionnaires and documentation. The results showed that the knowledge and behavior of nickel miners had a positive and significant effect on environmental management. Good knowledge of the mining environment improves environmental management, while environmentally friendly behavior of miners also contributes significantly in supporting sustainable environmental management. The implication of this study is the importance of increasing miners' knowledge and environmentally friendly behavior through training and company policies to maintain and preserve the environment.